Gut Akkermansia muciniphila ameliorates metabolic dysfunction-associated fatty liver disease by regulating the metabolism of L-aspartate via gut-liver axis - Rao, Yong; Kuang, Zhiqi; Li, Chan; Guo, Shiyao; Xu, Yaohao; Zhao, Dandan; Hu, Yutao; Song, Bingbing; Jiang, Zhi; Ge, Zhenhuang; Liu, Xiyuan; Li, Chengdao; et al. (Gut microbes, 2021)
The gut bacterium Akkermansia muciniphila has been increasingly recognized for its therapeutic potential in treating metabolic disorders, including obesity, diabetes, and metabolicdysfunction-associated fatty liver disease (MAFLD). However, its underlying mechanism involved in its well-known metabolic actions needs further evaluation. The present study explored the therapeutic effect and mechanism of A. muciniphila in intervening MAFLD by using a high-fat and high-cholesterol (HFC) diet induced obese mice model. Mice treated with A. muciniphila efficiently reversed MAFLD in the liver, such as hepatic steatosis, inflammatory, and liver injury. These therapeutic effects persisted after long-term drug withdrawal and were slightly weakened in the antibiotics-treated obese mice. A. muciniphila treatment efficiently increased mitochondrial oxidation and bile acid metabolism in the gut-liver axis, ameliorated oxidative stress-induced cell apoptosis in gut, leading to the reshaping of the gut microbiota composition. These metabolic improvements occurred with increased L-aspartate levels in the liver that transported from the gut. The administration of L-aspartate in vitro or in mice displayed the similar beneficial metabolic effects mentioned above and efficiently ameliorated MAFLD. Together, these data indicate that the anti-MAFLD activity of A. muciniphila correlated with lipid oxidation and improved gut-liver interactions through regulating the metabolism of L-aspartate. A. muciniphila could be a potential agent for clinical intervention in MAFLD.